(untitled) (Islamic Sciences Journal, 2023)
ABSTRACT Man, according to his nature, loves certainty in everything, especially in matters of belief, and takes various ways to remove doubts and illusions from his intellectual imagination. The Holy Qur’an paid great attention to this aspect, and urged the Muslim to have firm faith that would not be shaken by the likeness of skeptics, and he used the term “conjecture.” Which comes with the meaning of certainty in addition to the word certainty, and praised those who built their faith on certainties. The link between the words of suspicion and certainty is very strong in achieving faith, and this link goes back to the importance of the Arabic language in explaining the ways of knowing things, where the Holy Qur’an often uses these indicative words On certainty in the positions of the Islamic faith. It should be known that matters of belief cannot be built on speculations, rather they must be based on certainties, which emanate from definitive texts, because certainty alone is what saves its owner from peril and from falling into suspicions and illusions. This research comes as a study of the words of conjecture and certainty and their connection in verifying faith, and then arriving at the most important results desired in the research, if Allah willing.